(untitled) - George, Stephen (New York, 1992)
This guide demonstrates how the use of the Baldridge quality control system can help businesses grasp the elusive concepts of quality improvement. It demonstrates how to use the Baldridge application process to enhance the performance of any organization.
Keywords: Malcolm baldrige national quality award.,Total quality management; United states